Effect of Saccharomyces uvarum on lipid oxidation and carbonyl compounds in silver carp mince during cold storage. Issue 7 (25th June 2019) - Xu, Lina; Luo, Yu; Fu, Xiangjin; Luo, Feijun; Xu, Youzhi; Sun, Shuguo
Abstract: Fish lipid is highly susceptible to oxidation, resulting in accumulation of toxic substances reactive carbonyl compounds (RCCs), the reduction of nutritional value, and the production of odorous substances. In this study, the effect of yeast ( Saccharomyces uvarum ) on RCCs, fat acid composition, volatiles, and sensory traits in silver carp mince stored at 4°C was evaluated. Yeast eliminated malondialdehyde, 4‐hydroxyl‐2‐hexenal, and 4‐hydroxyl‐2‐nonenal by about 80%, 68%, and 60%, which increased by about 170%, 340%, and 300% in the control, respectively. Yeast helped retain about 80% of the polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), respectively; only about 53% and 46% of EPA and DHA, respectively, were maintained in the control. Yeast removed off‐odors hexanal, nonanal, and decenal, resulting in enhanced sensory traits. These findings were economically important for improving the quality of fish products. It might present an approach to improve the flavor of fish products. Abstract : Yeast eliminated MDA, HHE, and HNE in fish mince by about 80%, 68%, and 60%, helped retain about 80% of EPA and DHA in fish mince cold stored for 3 days. And the yeast removed a large part of volatiles that lead to off‐odors.